Benchmarking Pain Outcomes for Children with Sickle Cell Disease Hospitalized in a Tertiary Referral Pediatric Hospital. (2012) - Vijenthira, Abi; Stinson, Jennifer; Friedman, Jeremy; Palozzi, Lori; Taddio, Anna; Scolnik, Dennis; Victor, Charles; Kirby-Allen, Melanie; Campbell, Fiona
Abstract : BACKGROUND: Painful vaso-occlusive crisis (VOC) is the most common reason for hospitalization in children with sickle cell disease. OBJECTIVE: To benchmark pain outcomes in sickle cell disease, including process outcomes (eg, pain assessment and documentation practices, pain management interventions) and clinical outcomes (eg, pain intensity over hospital stay), to identify areas for improvement. METHODS: A retrospective study was conducted on electronic charts of children hospitalized with a primary diagnosis of VOC between July 2007 and August 2008. RESULTS: A convenience sample of 50 admissions was used. In terms of clinical outcomes, patients presented to the emergency department with an initial median pain intensity of 9/10 (interquartile range 8/10 to 10/10). Forty-three per cent had not used opioids for pain relief at home. The mean (± SD) length of stay was 4.0±2.3 days. For most patients, median scores for highest daily pain intensity remained moderate to high throughout hospitalization, although scores did decrease significantly per day of hospitalization. In terms of process outcomes, pain intensity was assessed according to hospital standards on 25% of days in both the emergency department and the ward. There was no discrepancy between prescribed and administered opioid doses and medication use. In 95% of cases, strong opioid use was in a subtherapeutic or low therapeutic dosage range. CONCLUSIONS: The results showed three areas to target for improvement: improved pain assessment and documentation using valid pain tools; more aggressive multimodal management for peak VOC pain; and better education and support for pain management at home. Further studies are required to evaluate optimal pain treatment practices.